The Moderating Role of Corporate Governance in the Relationship Between Corporate Social Responsibility and Firm Value - Made Dwipa Widiartana; Ni Made Adi Erawati (E-Jurnal Akuntansi, 2025)
This study aims to examine the impact of Corporate Social Responsibility (CSR) on firm value, with Good Corporate Governance (GCG) serving as a moderating variable. Transparency and corporate social responsibility have become increasingly significant due to their substantial influence on business perspectives and outcomes. The research focuses on mining companies over the period from 2019 to 2023. The sample comprises 19 companies, resulting in 95 observations across five years, selected using the purposive sampling method. The data were analyzed using Moderated Regression Analysis (MRA). The findings reveal that CSR has a positive effect on firm value, and this relationship is further strengthened by the implementation of effective GCG practices. The results indicate that robust GCG practices can mitigate potential negative impacts arising from managerial misconduct or CSR-related issues. This, in turn, fosters positive investor perceptions, thereby enhancing firm value.